Polycentric governance for small water supply systems: A case study in Kajiado, Kenya - Amarnath, Giriraj; Pahlke, Klaus Dieter; Barbara Schreiner; Emilian Mans; van Koppen, Barbara (2022)
The Water Integrity Network (WIN) conducted a study focusing on credible evidence on the impact of the Integrity Management Toolbox on Small Water Supply Systems at two levels, principally at the service delivery, governance and compliance with applicable rules and regulations. The subject of evaluation was the water supply system and the management model by which the water system is run (community group or water service provider) in Kajiado County, a pastoralist area that is mainly occupied by the Masaai. The evaluation considered differences in how the Integrity Management Toolbox was applied and compared these with the changes (service delivery, governance and compliance) achieved. From the findings, Water Integrity Network will draw lessons from implementation experience and make recommendations to improve effectiveness of the Integrity Management Toolbox on the quality of service delivery, governance improvements and compliance.'